Assessment of Readiness for Industry 4.0 Implementation in Ceramic Industry - Kellner, Tomas; Necas, Martin; Kanak, Michal; Kyncl, Martin; Kyncl, Jiri (Manufacturing Technology Journal, 2020)
This paper focuses on the implementation of principles of Industry 4.0 concept to the ceramic industry. The topic of this paper is to address the problematics of the implementation of processes and elements of digitization within the Industry 4.0 concept into the ceramic industry. Firstly, thorough literature and best-practice research will be discussed. Based on the state of current knowledge, the concept of the Industry 4.0 Readiness Model for Refractory will be presented. The model's main focus is on the readiness of current business structures, processes and technical and economical situation. It will provide the necessary analysis and insight into the potential company's processes and background. Based on this analysis, it will be possible to define the main obstacles for future digitalization and automation within Industry 4.0 the concept in Refractory industry. On the foundation of data obtained by Industry 4.0 Readiness Model for Refractory, it will be possible to implement the Industry 4.0 solutions with the highest added value to a specific company, based on its current state. The main purpose of this paper is to summarize and discuss key parameters and framework for Industry 4.0 Readiness Model for Refractory and its connection to future implementation of Industry 4.0 features within the ceramic industry.
Keywords: Industry 4.0; Smart Factory; Refractory Industry; Readiness Assessment; Assessment Model